2009
DOI: 10.1016/j.fertnstert.2008.07.1760
|View full text |Cite
|
Sign up to set email alerts
|

Cumulus cells and their extracellular matrix affect the quality of the spermatozoa penetrating the cumulus mass

Abstract: Both the cumulus matrix and the cumulus cells contribute to the effect of cumulus oophorus on spermatozoa penetrating through it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 59 publications
1
30
0
Order By: Relevance
“…In particular, in a video microscopic in vitro fertilization experiment, it was recently found that double transgenic male mice spermatozoa, expressing enhanced green fluorescent protein (EGFP) in their acrosomes and red fluorescent protein (Ds-Red2) in their midpiece, undergo AR before reaching the ZP ( Jin et al, 2011). In other words, it was shown that AR occurs during the interaction with cumulus and it is not necessary to penetrate ZP, thus confirming the role of receptors for cumulus extracellular matrix proteins observed in spermatozoa of several species (Barboni et al, 2001;Gadella, 2012;Hong et al, 2009). Furthermore, recently, the concept that the spermatozoa that have already undergone AR are unable to bind the ZP and have lost their fertilizing ability has been revamped.…”
Section: Introductionmentioning
confidence: 62%
“…In particular, in a video microscopic in vitro fertilization experiment, it was recently found that double transgenic male mice spermatozoa, expressing enhanced green fluorescent protein (EGFP) in their acrosomes and red fluorescent protein (Ds-Red2) in their midpiece, undergo AR before reaching the ZP ( Jin et al, 2011). In other words, it was shown that AR occurs during the interaction with cumulus and it is not necessary to penetrate ZP, thus confirming the role of receptors for cumulus extracellular matrix proteins observed in spermatozoa of several species (Barboni et al, 2001;Gadella, 2012;Hong et al, 2009). Furthermore, recently, the concept that the spermatozoa that have already undergone AR are unable to bind the ZP and have lost their fertilizing ability has been revamped.…”
Section: Introductionmentioning
confidence: 62%
“…In the presence of human cumulus oophorus, a significant enhancement of human sperm AR was observed after 5 h preincubation with the capacitation medium in vitro (Tesarík, 1985). A study examining the effect of cumulus matrix and cumulus cells on sperm penetration revealed that, compared to cell-depleted matrix, more sperm could penetrate the intact cumulus complex, with a higher percentage of normal morphology, AR and motility (Hong et al, 2009). Fragments of preovulatory human cumulus were washed 3 times and incubated for 24 h, and the spent media and washes were assayed for their ability to initiate human sperm AR in vitro.…”
Section: Facilitated Ar In the Presence Of Cumulus Layermentioning
confidence: 99%
“…The acquisition of hyperactivation is an absolute requirement for penetration of the cumulus, extracellular matrix and the ZP (41). Sperm able to traverse the cumulus oophorus have higher percentages of normal morphology and specific motility patterns, and this selection is aided both by the cumulus matrix and the cumulus cells (42). Moreover, sperm capable of binding to hyaluronic acid, the main component of the cumulus extracellular matrix, are mature, acrosome intact (43), and have a higher DNA integrity (44).…”
Section: Cumulus Oophorusmentioning
confidence: 99%